Preparation and characteristics of LiF:Mg,Cu,Na,Si thermoluminescent material - Ha, Vu Thi Thai; Hai, Nguyen Thi Quy; Long, Nguyen Ngoc; Vu, Le Van (VNU Journal of Science: Mathematics - Physics, 2007)
Abstract: